Immune analysis assessment of immunized hens with a complex of antigens by qualitative and quantitative testing of immunoglobulins obtained from their hyperimmune eggs - Mariana Oporanu; Madalina Tablica; Teodora Supeanu; Lucica Sima; Viorica Chiurciu; Constantin Chiurciu (Medicamentul Veterinar, 2019)
Immunoglobulins Y (IgY) are the main antibody synthesized by the body of birds, reptiles, amphibians and some fish species. In the last decades, IgY has been receiving growing attention from medical specialists. It presents a number of structural differences from mammalian IgG and multiple benefits compared to mammalian antibodies. IgY can be applicable in the diagnosis, prevention, and therapy of infectious diseases of pathogenic bacteria, fungi or viruses. This study aimed to evaluate the specific antibody titer against 18 antigens for a period of 13 months. Throughout the experiment, ELISA assays were performed to determine the total immunoglobulin concentration in the obtained hyperimmune eggs and the specificity of the extracted IgG to each antigen.